The Impact of the Two-Child Policy on Urban Family Dynamics in Beijing: Parental Roles, Child Development, and Family Economic Strategies - Jun Yu (Studies in Social Science & Humanities, 2024)
The implementation of the Two-Child Policy in Beijing has significantly influenced urban family dynamics, encompassing changes in parental roles, child development, financial strategies, and societal attitudes. This study explores these multifaceted impacts through various lenses, including the evolution of parental roles towards more equitable childcare responsibilities, the developmental outcomes of first-born and second-born children, and the economic adjustments families make to accommodate increased household expenses. It also examines the role of extended family and community support in alleviating the pressures associated with raising multiple children, as well as the shifting societal attitudes towards larger families. By analyzing these dimensions, the study provides a comprehensive understanding of how the Two-Child Policy is reshaping family life in urban Beijing, highlighting both the challenges and opportunities it presents.